The safety and effectiveness of volumetric magnetic resonance-guided high-intensity focused ultrasound treatment of symptomatic uterine fibroids: early clinical experience in China - Chen, Rui (J Ther Ultrasound, 2016)
BACKGROUND: Uterine fibroids are the most common benign tumor in women, and surgical intervention is still the main fibroid treatment. Patient demands have encouraged development of less-invasive methods such as high-intensity focused ultrasound (HIFU). This study aimed to evaluate the safety and effectiveness of magnetic resonance-guided high-intensity focused ultrasound therapy using a volumetric ablation technique in the treatment of symptomatic uterine fibroids in China. METHODS: One hundred and seven patients were enrolled and treated with magnetic resonance-guided high-intensity focused ultrasound in this study. Clinical efficacy was based on the proportion of patients with fibroid shrinkage (10 % volume reduction or more compared to baseline) at 6 months post treatment as measured with magnetic resonance imaging. The quality of life and symptom outcome was assessed using the uterine fibroid symptom and quality of life questionnaire with symptom severity scoring. Safety was primarily assessed by evaluating the reported adverse events. RESULTS: Ninety nine of the 107 treated patients had fibroid shrinkage at 6 months post treatment. Resulting in an overall 93 % (95 % confidence interval 86–97 %) treatment success rate, p value <0.001; the symptom severity scoring and health-related quality of life at 6 months was statistically different from the screening symptom severity scoring at 0.05 level. Of 366 adverse events reported, there were no study procedure-related or device-related serious adverse events were in the study. CONCLUSIONS: This study demonstrated that the volumetric magnetic resonance-guided high-intensity focused ultrasound device is safe and technically effective and can be utilized in clinically efficient treatments of symptomatic uterine fibroids. TRIAL REGISTRATION: NCT01588899